Membangun Sistem Informasi Inventaris Laboratorium Jurusan Administrasi Bisnis Berbasis PHP Dan MySQL Dengan Framework Laravel Dan Bootstrap - Muhammad, Said; Yunida, Riswan; Irwandi, Agus; Indera, Rahma; Prihatin, Eko Sabar (P3M Politeknik Negeri Banjarmasin, 2021)
The development of information technology is currently growing rapidly, one of which is in terms of information management. By utilizing information technology support, information processing can now be done quickly, and can be presented globally by utilizing the internet network. The website is a media that is currently widely used as a tool to provide services and information [1]. In its activities in the process of data collection and equipment inventory reports, the Laboratory of Business Administration Department has not implemented an optimal computerized system. So that in producing all accurate and precise reports require a relatively long time or incomplete reports produced. Inventory Information Systems can Increase the efficiency and effectiveness of data accurately Thus required testing of the application system aims to obtain certainty of the functional truth of the system and the needs of users based on the literature that supports it. In this research software testing uses white box testing and black box testing